Efficacy of the LMA-ClassicTM and LMA ProsealTM in Children Undergoing Elective Surgery under General Anaesthesia - Pratik M Doshi; Ashish B Shah (Academia Anesthesiologica International, 2019)
Background: The LMA-ProsealTM is a second generation supraglottic airway device with modified cuff and a drainage tube, designed for better seal with both the respiratory and gastrointestinal tracts, notwithstanding the access to the alimentary tract. The present study is planned to compare efficacy of the LMA-ClassicTM and LMA ProsealTM in children undergoing elective surgery under general anaesthesia. Subjects and Methods: 120 children belonging to American Society of Anesthesiologists Physical Status 1 and 2, aged 3 to 15 years and weighing 5 to 45 kg undergoing elective surgery in the supine position were randomized for airway management with the LMA-ClassicTM or LMA ProsealTM by computer-generated random assignments. Results: There was no difference between LMA ClassicTM and LMA ProsealTM with regard to ease of insertion, number of attempts for insertion, device positional stability, airway trauma and hemodynamic changes. Conclusion: The LMA-ProsealTM has advantages over LMA-ClassicTM like the placement of gastric tube, adequate ventilation and oxygenation without any gastric distension. The complications of usage of the LMA are minimal and similar in both the devices.